'The Black Pit:' Power and Pitfalls of Digital FDI and Cross-Border Data Flows. Issue 1 (February 2023) - Chaisse, Julien
Abstract: In today's data-driven economy, data have been dubbed as the new oil . Hence, a close relationship is shared between the increasing amounts of international investments and the increasing volumes of cross-border data flows. The aim of this article is to discuss the legal aspects of the new data paradigm in the international economy and place this discussion in the larger framework of globalization and the Liberal International Order. The central thesis of the article revolves around the crucial role played by domestic laws in the fragmentation of international investment law. The article further discusses the interplay between national and international legal landscapes and how the changing nature of the Liberal International Order is affecting the flow of data across borders. In this context, it also discusses the issues that are presented by a lack of any comprehensive international framework governing Cross-Border Data Flows. The need to update existing agreements and laws in order to factor in digital investment is also highlighted.